Sexual Behavior Reflected In Saman Novel By Ayu Utami (1998): A Psychoanalytic Approach - Harjatmiko, Ade Inmay; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2015)
Novel Saman tells the story of sexual problems, especially in the female figures. This study is important because it tries to uncover the sexual behaviors of the characters. This study concerns about the actual sexual behavior in society. The problem studied in this research are how the forms of sexual perversion and the factors behind sexual perversion in novel Saman by Ayu Utami. The approach used in this study is the psychoanalytic approach to literature. This approach aims to determine the forms and the factors that cause the occurrence of sexual deviation behavior of female characters in the novel Saman by Ayu Utami. The target of this research is the forms of sexual behavior and the factors that cause deviation sexual behavior in novel Saman by Ayu Utami. Data analysis technique used is to describe and analyze the leaders through a psychoanalytic approach. The results of this study indicate that female characters in the novel novel Saman by Ayu Utami has a deviant sexual behavior that is adultery, zoofilia, masturbation, rape, promiscuity, and bisexuality. The factors underlying the occurrence of sexually deviant behavior in novel Saman by Ayu Utami that encouragement of the self, environmental influences, cultural influences and a lack of understanding of the teachings of religions practiced. Based on the analysis , the authors convey suggestions include novel Saman research using psychological theory literature can be used as an additional reference for students who are doing similar research and can be used as an object of study by using other theories.